Revalorización de la marca de la revista New Magazine en el mercado de la provincia de Manabí - Falcones Zambrano, Cristhian Rafael (2014)
This research was carried out in Manta, Portoviejo, and Bolívar canton in order to reposition the New Magazine brand in the market of the province of Manabí. The methodology used in the research was the deductive, analytical and quantitative method. Tools were applied as survey to the inhabitants of the mentioned cantons with a range between 18 to 65 years of age, allowing the identification of potential customers and thus corresponding segmentation to then proceed with the execution of market research, then perform direct observation by the perception of the different magazines on the market allowing to know the real situation of the magazine. The market study established that the main competitors are; Panorama and home consumers identified in the market segmentation, substitute products are identified in digital magazines. Brand strengths, weaknesses, threats and opportunities were defined after reviewing the current situation through a SWOT analysis. The strategic plan established mission and vision, strategic objectives; it was developed a marketing plan by defining the characteristics of the magazine, price, and distribution channel from the company directly to the reader through shopping stores and gas station service, it will also run advertising in radio and internet in order to penetrate into the minds of the consumers.